1988
DOI: 10.1002/bjs.1800750818
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the analgesic efficacy of nefopam hydrochloride after upper abdominal surgery: A study using patient controlled analgesia

Abstract: A randomized, double-blind, placebo-controlled study was performed to assess the analgesic efficacy of intramuscular nefopam hydrochloride after upper abdominal surgery. Patients received either 20 mg nefopam (n = 23) or matching placebo (n = 26), 90 min before surgery, immediately after surgery, and 6, 12 and 18 h after the end of surgery. The 24-h morphine requirements were measured using a patient-controlled analgesia system delivering on-demand intravenous bolus doses of morphine. Pain was assessed using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 15 publications
4
42
1
Order By: Relevance
“…every 6 h for 24 h (cumulative dose, 100 mg) in patients undergoing upper abdominal surgery, 18 or 20 mg i.v. every 4 h for 24 h (cumulative dose, 120 mg) in patients undergoing hepatic resection, 20 or hip arthroplasty.…”
Section: Pain Outcomesmentioning
confidence: 99%
“…every 6 h for 24 h (cumulative dose, 100 mg) in patients undergoing upper abdominal surgery, 18 or 20 mg i.v. every 4 h for 24 h (cumulative dose, 120 mg) in patients undergoing hepatic resection, 20 or hip arthroplasty.…”
Section: Pain Outcomesmentioning
confidence: 99%
“…5 Studies have consistently demonstrated a 30-40% decrease in postoperative opioid consumption when nefopam is used following abdominal or orthopaedic surgery. 6,7 Unlike nonsteroidal anti-inflammatory drugs, nefopam has no effect on platelet function, 8 and (in contrast to opioids) does not increase the risk of respiratory depression. 9 In addition, nefopam has been shown to result in decreased morphine consumption when used as a coanalgesic following abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The nefopam-induced strong inhibition of nociceptive reflexes in volunteers confirmed its central action site 9. Several studies demonstrated its efficacy during the postoperative period 4 16 17. The usual IV dose of nefopam is 20 mg, which has an analgesic potency equivalent to 6–12 mg of morphine 18 19.…”
Section: Introductionmentioning
confidence: 87%